Dry eye disease in astronauts: a narrative review - Timon Ax; Timon Ax; Bergita Ganse; Bergita Ganse; Fabian N. Fries; Fabian N. Fries; Nóra Szentmáry; Cintia S. de Paiva; Francesc March de Ribot; Slade O. Jensen; Slade O. Jensen; Berthold Seitz; et al. (Frontiers in Physiology, 2023)
Long-duration spaceflight can have adverse effects on human health. One of the most common ocular conditions experienced by astronauts is dry eye disease (DED). Symptoms of DED include feelings of eye irritation, eye strain, foreign body sensation and blurred vision. Over 30% of International Space Station expedition crew members reported irritation and foreign body sensation. We reviewed the current literature on the prevalence and mechanisms of DED in astronauts and its potential implications for long-duration spaceflight, including the influence of environmental factors, such as microgravity and fluid shift on tear film physiology in space. DED has negative effects on astronaut performance, which is why there is a need for further research into the pathophysiology and countermeasures. As an in-flight countermeasure, neurostimulation seems to be among the most promising options.